1998
DOI: 10.1177/1046496498293005
|View full text |Cite
|
Sign up to set email alerts
|

Member Perceptions of Internal Group Dynamics and Productivity

Abstract: The purpose of thisfield research was to explore the relationship between member perceptions of internal group dynamics and group productivity. Forty-four work groups participated in this study. Significant relationships were noted between member perceptions of internal group dynamics and group levels of productivity as measured by the organizations as well as by members 'perceptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 29 publications
5
47
0
Order By: Relevance
“…Studies of group development span half a century and include impressionistic studies, which rely on experiences and reflections of observers (e.g., Bennis & Shepard, 1956;Bion, 1961), empirical studies using observational systems (e.g., Bales, 1950;Gersick, 1988), studies based on archi-val materials (e.g., Worchel, 1994), and cross-sectional survey studies (e.g., Wheelan, Murphy, Tsumura, & Kline, 1998).…”
Section: Systematic Change Over Timementioning
confidence: 99%
“…Studies of group development span half a century and include impressionistic studies, which rely on experiences and reflections of observers (e.g., Bennis & Shepard, 1956;Bion, 1961), empirical studies using observational systems (e.g., Bales, 1950;Gersick, 1988), studies based on archi-val materials (e.g., Worchel, 1994), and cross-sectional survey studies (e.g., Wheelan, Murphy, Tsumura, & Kline, 1998).…”
Section: Systematic Change Over Timementioning
confidence: 99%
“…Nevertheless, meta-analyses [2,27] underline the significance of this study for cognitive, affective, process-and personal-measures to describe what has been construed to be an 'effective team' [1]. Several studies have demonstrated the association between team-development and performance [1,[15][16][17]28,29], and also between team-development and affective indications such as work-satisfaction, emotional exhaustion and sick leave [18,19,30]. Effective teams are characterized by behaviors such as information exchange, functional leadership alternation and metacognition centered around the groups' work, problems and solutions, that include process-and cognitive-indices as outcomes [21].…”
Section: Discussionmentioning
confidence: 99%
“…A further limitation pertains to the outcome measures, GDQ, presented as questionnaire allowing it to be colored by group-members' subjective reporting [2]. Nevertheless, GDQ offers a well-established instrument with high reliability and validity [8] with several studies presenting high concordance between GDQ estimations and objective performance measures [1,[15][16][17]29]. The study gives a 'half-way' mark of the complete project with relatively limited sample which also may have lack of sufficient statistical power.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This development towards a higher level may be facilitated by various interventions targeting the needs of the group [2]. The increase of a group's developmental level has been shown to affect, above all, a group's productivity level [23]. To achieve a higher level of group development an intervention has to take into account the group's abilities and needs.…”
Section: Group Developmentmentioning
confidence: 99%